Antibiotic Resistance of Acinetobacter baumannii Strains Isolated in 2015-2018 Years - Tuncer Ozekinci; Zafer Habip; Neslihan Onder; Mücahıde Esra Koçoglu (Van Tıp Dergisi, 2020)
INTRODUCTION: Treatment of Acinetobacter baumannii infections has become increasingly diffucult, due to the high resistance rates against commonly administreted antibiotics. The aim of this study is to detect the antibiotic resistance of A.baumannii strains isolated from clinical specimens in years 2015-2018 METHODS: Antibiotic resistance of 1148 A.baumannii strains isolated from various clinical specimens between January 1, 2015 and December 31, 2018 was investigated retrospectively. Bacteria were identified using MALDI-TOF-MS (Biomerieux Inc., France) system. Antibiotic susceptibility of the strains were performed with Vitek 2 (Biomerieux Inc., Fransa) automated system. RESULTS: In 1148 of the clinical specimens A.baumannii was isolated. Total antibiotic resistance of isolated strains within these four years were determined as 83.5% for piperacillin/tazobactam, 81.6% for ceftazidime, 81.7% for meropenem, 80.5% for ciprofloxacin, 46.6% for amikacin, 50.4% for gentamicin, 59% for trimethoprim-sulfamethoxazole, 22% for tigecycline and 1.8% for colistin. Colistin resistance was found to be 0.8%, 0%, 2.9% and 3.2% for 2015, 2016, 2017 and 2018, respectively. Tigecycline resistance was determined to be 23.5%, 12.8%, 18.9% and 29.8%, respectively. DISCUSSION AND CONCLUSION: In our study, colistin and tigecycline were the most effective antibiotics against A.baumanniis trains.However, it is noteworthy that tigecycline resistance increased over the years and colistin resistance was determined. Because of these increase rates, treatment options for clinicians are decreasing day by day. Therefore, it was thought that it is important to examine its own antibiotic resistance profile by each hospital in order to guide clinician for the empiricial treatment of serious infections which can be life threatening especially like Acinetobacter infections.